PERANAN LOCUS OF CONTROL DAN JUSTICE TERHADAP ESKALASI KOMITMEN DALAM PENGAMBILAN KEPUTUSAN PENGANGGARAN MODAL - LOEKMAN, ANDREW (: 2303-1719)
Large and small companies use the capital budgeting as one of the first steps in carrying out business activities. Performance throughout the company infrastructure directly related to the preparation of the capital budgeting. As a result of conflicts of interest arise when an individual is contracted to act in an effort to meet the economic interests of the company, while the individual is motivated to maximize its own economic interests. Locus of control and justice is one system that acts as a watchdog and protector for the company's internal systems as well as the individual who is in the company. The system is set up not merely to protect the other systems, but also to protect individuals from injustice that often occurs when a company has a number of relative human resources many. Locus of control as an action in which individuals connect the events in his life by the actions or forces beyond his control. The concept of locus of control has a theoretical background in social learning theory. Escalation of commitment is the improvement of the previous decision despite evidence that the decision was probably wrong. Justice is justice in that organization refers to the fairness (equity) in the workplace and is composed of distributive, procedural and interactional justice. Interactional justice as the degree to which people are affected by the decision capital budgeting being run with dignity and respect,